Implementation of Zachman Framework on Hotel Online Reservation System - Nurul Fadilah Aswar; Matthew Olufemi Adio (Indonesian Journal of Enterprise Architecture, 2024)
mplementation of Zachman Framework on Online Reservation System at Hotel Claro Makassar is a strategic effort made by the hotel to improve operational efficiency and customer experience. In the competitive environment of the hospitality industry, an integrated online reservation system is an important requirement for modern hotels. This research aims to investigate and analyze the benefits of using Zachman Framework in developing a comprehensive and effective online reservation system at Hotel Claro Makassar. Zachman Framework is used as a structured architecture framework, which helps in designing, implementing, and managing information systems by considering a variety of different perspectives. This research methodology involves the stages of needs analysis, system design, program implementation, and testing using white box and black box methods. The Zachman Framework is used as a guide to identify and understand important elements in an online hotel reservation system, including problem identification, business scope, governance, information model, technology, and system deployment. The result of this research is an online hotel reservation system that can facilitate users in searching, reserving, and canceling rooms online, as well as allowing hotel management to manage reservation data, room availability, and payment transactions efficiently. The implementation of this system is expected to improve the efficiency of hotel operations and provide a better experience for users in making hotel reservations online.